Determination of analytical signal true form in shape of peak de-formed by base line and/or other component signal; International Conference Analytical Chemistry, Moscow, June 15 - 21 1997; Vol. 1 - Stromberg A. G. Armin Genrikhovich (1997, 1997)
В фонде НТБ ТПУ отсутствует